Effects by Different Microstructure and Texture of Hot Band on the Evolution of Microstructure and Texture after Cold Rolling and Final Annealing of Ferritic FeSi Steels (Journal of Material Science and Technology Research, 2019)
It is well established that there is an interplay and interaction between the processing steps at fabrication of non-oriented electrical steels: hot rolling, cold rolling and annealing with respect to the evolution of the microstructure and texture. In this paper we will analyse in detail by optical microscopy and EBSD-measurements the influence of the microstructure of hot band prepared in different ways on the deformation structure after cold rolling and finally the evolution of microstructure as well as texture at final annealing due to recrystallization followed by grain growth. It will be demonstrated that the microstructure of the hot band effects the start of the recrystallization and finally the start of the grain growth at final annealing. The evolution of the microstructure at the stage of recrystallization is rather inhomogeneous across the thickness. This results from the complex deformation substructures after cold rolling. It will be pointed out that an explanation of the texture evolution at recrystallization only by in-plane compression stress fails. The inclusion of shear stress may explain the observed figure for the texture. The grain growth, which is necessary for the non-oriented electrical steels to reach the desired low values of specific magnetic losses, is finally the dominant process at the relevant higher annealing temperatures. The evolution of texture at recrystallization is different from those at grain growth.